2019
DOI: 10.1103/physrevx.9.031045
|View full text |Cite
|
Sign up to set email alerts
|

A Ten-Qubit Solid-State Spin Register with Quantum Memory up to One Minute

Abstract: Spins associated to single defects in solids provide promising qubits for quantum information processing and quantum networks. Recent experiments have demonstrated long coherence times, high-fidelity operations and long-range entanglement. However, control has so far been limited to a few qubits, with entangled states of three spins demonstrated. Realizing larger multi-qubit registers is challenging due to the need for quantum gates that avoid crosstalk and protect the coherence of the complete register. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
465
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(486 citation statements)
references
References 72 publications
(95 reference statements)
1
465
0
Order By: Relevance
“…3. This platform is a few (about 10 [6]) qubit quantum computer with an optical interface capable of executing arbitrary gates and measurements. It has been recently demonstrated that NV centres are capable of memory lifetimes approaching one minute [6] in nodes not yet interfaced to the network.…”
Section: Elements Of a Quantum Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…3. This platform is a few (about 10 [6]) qubit quantum computer with an optical interface capable of executing arbitrary gates and measurements. It has been recently demonstrated that NV centres are capable of memory lifetimes approaching one minute [6] in nodes not yet interfaced to the network.…”
Section: Elements Of a Quantum Networkmentioning
confidence: 99%
“…This platform is a few (about 10 [6]) qubit quantum computer with an optical interface capable of executing arbitrary gates and measurements. It has been recently demonstrated that NV centres are capable of memory lifetimes approaching one minute [6] in nodes not yet interfaced to the network. Other platforms exist that are similar on the conceptual level with similar capabilities such as ion traps [33] and neutral atoms [49] (see Table 1 for current parameter trade-offs).…”
Section: Elements Of a Quantum Networkmentioning
confidence: 99%
“…The part H N thereby only entails an energy shift A N /2π = ±2. 16 MHz of the electronic m s = ±1 states due to the hyperfine interaction [33,49]. The hyperfine tensor A, on the other hand, describes the dipoledipole interaction between the NV-center electron spin and the carbon nuclear spin.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…While compressed sensing techniques can significantly improve the efficiency of reconstructing low-rank quantum states [2][3][4][5][6][7][8][9][10][11], the problem of identifying an arbitrary state of a complex quantum system with limited measurement access (e.g., to a single qubit only) remains [12][13][14]. For example, one task of practical importance in the development of solid-state quantum devices [15][16][17][18][19] is the complete characterization of coupled spin states. However, when nuclear spins are involved, access to the full system is limited due to their small magnetic moment.…”
mentioning
confidence: 99%
“…However, this technique is limited by the short photo-excited triplet state lifetime, requiring fast polarisation transfer or weakly coupled nuclear spins [32]. A more sophisticated alternative is to use dynamical decoupling sequences to target individual nuclear spins one by one, initialising them in a well defined state [21,23,33]. In addition to improving the coherence of the electron spin, these techniques also enable full coherent control of the individual nuclear spins.…”
Section: Introductionmentioning
confidence: 99%